2017
DOI: 10.1007/978-981-10-3233-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Gene Bookmarking: An Epigenetic Mechanism for Coordination of Lineage Commitment, Cell Identity and Cell Growth

Abstract: Epigenetic control of gene expression contributes to dynamic responsiveness of cellular processes that include cell cycle, cell growth and differentiation. Mitotic gene bookmarking, retention of sequence-specific transcription factors at target gene loci, including the RUNX regulatory proteins, provide a novel dimension to epigenetic regulation that sustains cellular identity in progeny cells following cell division. Runx transcription factor retention during mitosis coordinates physiological control of cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Recent studies have shown that TFs binding to mitotic chromosomes are rather common 26,61 , and these were proposed to play a role in cell fate maintenance by controlling gene reactivation early during mitotic exit 31,34,39,62 . Furthermore, the presence of SOX2 and OCT4 at the M-G1 transition was shown to be required for their role in regulating ES cell fate decisions 32,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that TFs binding to mitotic chromosomes are rather common 26,61 , and these were proposed to play a role in cell fate maintenance by controlling gene reactivation early during mitotic exit 31,34,39,62 . Furthermore, the presence of SOX2 and OCT4 at the M-G1 transition was shown to be required for their role in regulating ES cell fate decisions 32,63 .…”
Section: Discussionmentioning
confidence: 99%
“…While it has long been thought that most TFs are excluded from mitotic chromosomes, more recent studies have shown that mitotic chromosome binding of TFs is rather common (Zaidi et al, 2017;Raccaud and Suter, 2017). TFs enriched on mitotic chromosomes were proposed to play a role in maintenance of cell fate by controlling gene reactivation early during mitotic exit (Caravaca et al, 2013;Kadauke et al, 2012;Lake et al, 2014;Zaret, 2014), and the presence of SOX2 and OCT4 at the M-G1 transition was shown to be required for their role in regulating ES cell fate decisions (Deluz et al, 2016;Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CpG methylation of specific promoters selectively silences the expression of tissue-specific genes (Fischle et al, 2003; He et al, 2008). And mitotic bookmarking, the retention of transcription factors at gene loci on chromosomes during cell division, epigenetically sustains RNA polymerase I and II control of cell growth and phenotype in normal and cancer cells(Ali et al, 2008; Arampatzi et al, 2013; Arora et al, 2016; Bakshi et al, 2008; Caravaca et al, 2013; Festuccia et al, 2016; John and Workman, 1998; Kadauke and Blobel, 2013; Kadauke et al, 2012; Kelly and Jones, 2011; Lake et al, 2014; Lerner et al, 2016; Liu et al, 2017; Lodhi et al, 2014, 2016; Lopez-Camacho et al, 2014; Pockwinse et al, 2011; Sarge and Park-Sarge, 2009; Teves et al, 2016; Verdeguer et al, 2010; Young et al, 2007a, 2007b; Zaidi et al, 2010a, 2010b, 2011b, 2014b, 2017a, 2017b; Zaret, 2014; Zhao et al, 2011). The significance of mitotic bookmarking is reinforced by a recent report from the Tjian laboratory that most transcription factors are significantly enriched on mitotic chromosomes (Teves et al, 2016).…”
Section: Gene Expression In Biological Control and Cancer In The Cmentioning
confidence: 99%
“…Persistence of cell identity requires post-mitotic restoration of nuclear organization and assembly of regulatory complexes. It has been conclusively demonstrated that RUNX proteins, as well as myogenic and adipogenic transcription factors that determine lin eage commitment, remain bound to their target genes, including rRNA genes, on mitotic chromosomes(Ali et al, 2010; Young et al, 2007a, 2007b; Zaidi et al, 2003, 2010b, 2017b). It has been established that RUNX2 remains associated with both RNA polymerase I and II-transcribed genes during mitosis (Young et al, 2007a, 2007b).…”
Section: The Regulatory Landscape Of the Cancer Cell Nucleusmentioning
confidence: 99%